2022
DOI: 10.3390/pharmaceutics14071503
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Blood Brain Barrier with an Electropermanent Magnet System

Abstract: Opening the blood brain barrier (BBB) under imaging guidance may be useful for the treatment of many brain disorders. Rapidly applied magnetic fields have the potential to generate electric fields in brain tissue that, if properly timed, may enable safe and effective BBB opening. By tuning magnetic pulses generated by a novel electropermanent magnet (EPM) array, we demonstrate the opening of tight junctions in a BBB model culture in vitro, and show that induced monophasic electrical pulses are more effective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…TTFields have not been approved for use in pediatric cohorts yet with clinical trials solely focused on adults highlighting its value as a potential treatment with minimal cytotoxicity (114,115). Pulsed electric fields have also been implicated in vitro and in vivo with transiently opening the BBB and may be suitable for enhancing drug bioavailability (116)(117)(118).…”
Section: Tumor Treating Fieldsmentioning
confidence: 99%
“…TTFields have not been approved for use in pediatric cohorts yet with clinical trials solely focused on adults highlighting its value as a potential treatment with minimal cytotoxicity (114,115). Pulsed electric fields have also been implicated in vitro and in vivo with transiently opening the BBB and may be suitable for enhancing drug bioavailability (116)(117)(118).…”
Section: Tumor Treating Fieldsmentioning
confidence: 99%
“…Thus, POH underlies its ability to overcome the obstacles placed by different types of biological barriers and accordingly shape its multifaceted promise in the drug development for cancer therapy [3]. In a novel approach, Jafari et al demonstrated proof-of-principle of a hybrid electropermanent magnets (EPM)-based device for temporarily opening the BBB using both an in vitro cell culture and an in vivo mice model [4]. This technique is useful for safe and effective drug transport across the BBB and can selectively target different parts of the brain by tailoring electrical waveforms [4].…”
mentioning
confidence: 99%
“…In a novel approach, Jafari et al demonstrated proof-of-principle of a hybrid electropermanent magnets (EPM)-based device for temporarily opening the BBB using both an in vitro cell culture and an in vivo mice model [4]. This technique is useful for safe and effective drug transport across the BBB and can selectively target different parts of the brain by tailoring electrical waveforms [4].…”
mentioning
confidence: 99%